Spanish workers (circular)
Telegraphic Address: TRADUNIC, SOWEST LONDON Telephone: Victoria 6261 (4 lines) The Trades Union Congress General Secretary SIR WALTER CITRINE K.B.E. Your Ref: Our Ref: WMC/HVT/RC/67. Department Secretary's TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. Dear Sir (Madam), "SPANISH WORKERS". We wish to convey to you our very best thanks for the contribution you have sent to the above Fund. We can assure you that it is very much appreciated and will be used to the best possible advantage. Enclosed herewith is our official receipt for the amount sent. Yours sincerely, ENCL. Receipt. 292/946/29/99